Influence of the microstructure on the corrosion behaviour of a shape memory Cu–Al–Be alloy in a marine environment - Montecinos Espinoza, Susana de Los Angeles (2011)
The influence of the microstructure on the corrosion behaviour of a shape memory Cu–11.40Al–0.55Be (wt.%) polycrystalline alloy in 3.5% NaCl has been studied by microscopical examinations, spectroscopical and X-ray diffraction measurements, and electrochemical tests. Chloride environment can produce a dealuminization attack, and the corrosion behaviour is affected by the alloy microstructural conditions. After long times of immersion, the single β phase microstructure suffers localized corrosion in some regions but dealuminization is generalized on the whole surface. However, in the (β + γ2) microstructure, preferential dissolution of γ2 dendritic precipitates occurs, which seems to protect β matrix from dealloying.